Miejsce pracy w systemie wartości. Wyzwania wynikające z rozwoju technologii cyfrowych - Walczak-Duraj, Danuta (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2019)
The considerations contained in this study focus on two leading and interrelated issues. On the one hand, they relate to the workplace in the Poles’ system of values, on the other they deal with changes taking place in the contemporary labor markets caused by the influence of digital technologies, especially an artificial intelligence. Changing not only the content of the work but also the way it is done, will not be without influence both on attitudes towards work as significant value in human life so far, as well as on changes in leading personality profiles. In the existing scenarios regarding the future of work, one can find very different forecasts for the development of labor markets, the desired shape of the axionormative order of a society of the near future, algorithms increasingly firmly rooted in civilization. In this context, the postulate is increasingly raised that the concept of work, understood both as a value and the specific form of human activity, covers a wide variety of activities, including unpaid work and work without charge, and refers to service, care or educational work performed for the family, community local and also to the various forms of non-employee volunteering.